Cinema Square Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Fitrah Ramadhani Syam; Muhammad Rijal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Cinema square is a surrounding which has some activities inside the open area such as theatre and plaza. Cinema is included to someone’s choice to free from full activity. The unres tricted style of this cinema square is coherent to the design principlies of postmodern architecture. Postmodern architecture emerged as a liberation act of modern architecture. By using postmodern architecture as an approachment to design Cinema Square in Pekanbaru, therefore the concept of